Baseline associations of office and ambulatory blood pressure monitoring with cognitive function and dementia prevalence. - Melgarejo, Jesus D; Patil, Dhrumil; Charisis, Sokratis; Vatcheva, Kristina P; Mejia-Arango, Silvia; Mena, Luis J; Satizabal, Claudia L; Gaona, Ciro; Silva, Egle; Manusov, Eron; Lee, Joseph H; Terwilliger, Joseph D; et al. (J Alzheimers Dis, 2025)
BackgroundHigh blood pressure has been associated with dementia prevalence and incident. However, it is unclear the relationship of office and ambulatory BP monitoring with cognitive function and dementia and in particular, it remains unknown whether ambulatory BP variability relates to dementia.ObjectiveTo investigate the associations of office and 24-h blood pressure (BP) with cognitive function and dementia prevalence.MethodsCross-sectional population-based study of 1435 participants aged ≥40 years with office BP/24-h BP, and cognitive assessments (Mini-Mental State Examination [MMSE] and Selective Reminding Test [SRT]). Dementia was diagnosed with a clinical dementia rating ≥1.0. Statistics included logistic and linear regression models.ResultsThe mean age was 63.8 ± 10.3 years old and 995 (69.3%) were women. Out of the 1435 participants, 46 (3.20%) had dementia at baseline. Office and 24-h BP levels were not associated with dementia but with one SRT. Increasing 24-h systolic BP variability was associated with lower MMSE (adjusted mean, -0.08; 95% confidence interval [CI], -0.13, -0.03), and SRT (adjusted means ranged from -0.13 to -0.06; 95% CI ranging from -0.19 to -0.01) scores and 1.48-fold greater odds of dementia (95% CI, 1.09-2.02) regardless of BP level.ConclusionsElevated 24-h BP variability, not the BP level, seems to have a stronger association with lower cognitive function and dementia prevalence. Prospective studies are needed to address whether 24-h BP variability relates to cognitive decline and dementia incidence.